2017
DOI: 10.1681/asn.2016030343
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Factor B and Anti-C3b Autoantibodies in C3 Glomerulopathy and Ig-Associated Membranoproliferative GN

Abstract: In C3 glomerulopathy (C3G), the alternative pathway of complement is frequently overactivated by autoantibodies that stabilize the C3 convertase C3bBb. Anti-C3b and anti-factor B (anti-FB) IgG have been reported in three patients with C3G. We screened a cohort of 141 patients with C3G and Ig-associated membranoproliferative GN (Ig-MPGN) for anti-FB and anti-C3b autoantibodies using ELISA. We identified seven patients with anti-FB IgG, three patients with anti-C3b IgG, and five patients with anti-FB and anti-C3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
4
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 25 publications
2
80
4
1
Order By: Relevance
“…3 Significantly different from double positive patients. 4 Significantly different from C3NeF positive patients. LPV: likely pathogenic variant; C3NeF: C3 nephritic factor; C4NeF: C4 nephritic factor.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…3 Significantly different from double positive patients. 4 Significantly different from C3NeF positive patients. LPV: likely pathogenic variant; C3NeF: C3 nephritic factor; C4NeF: C4 nephritic factor.…”
Section: Discussionmentioning
confidence: 95%
“…Autoantibodies against complement components occur in a significant proportion of cases with C3G or IC-MPGN, although only a few large-scale studies have analyzed their presence in these conditions. Case reports [4,12,16,21,23,24] and case series studies [2], [5,31,32] described the presence of nephritic factors and other complement autoantibodies, but still, approximately 30 to 60% of the C3G cases remain without identified pathogenic factors (autoantibodies to complement components or pathogenic variants of disease-associated complement genes).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, NeFs against the classic/lectin pathway C3 convertase (known as C4NeFs) have also been described [20]. Other autoantibodies include anti-FH, anti-FB, and anti-C3b [31]. However, while the pathogenic role of NeFs in C3G is well established, still there are some uncertainties concerning the best diagnostic methods for their detection, their correlation with the clinical course of the disease, and the most effective therapy to target the production of these autoantibodies [20].…”
Section: Pathogenesismentioning
confidence: 99%
“…Their study revealed that they prevented the spontaneous dissociation of the C3 convertase of the AP and increased its normal half-life, thus causing systemic complement activation in the patient [30]. Additional patients with anti-FB and anti-C3b autoantibodies have since been reported in C3G and Ig-Associated Membranoproliferative Glomerulonephritis cohorts supporting their pathological role in the dysregulation of the AP [31,32]. Therefore, further studies are needed in order to clarify if anti-FB and anti-C3b autoantibodies have a primary mechanistic role in the pathology of the lipodystrophy or if they rather secondarily arise as a consequence of the increase in circulating complement proteins produced due to unabated complement activation in the presence of C3NeF.…”
Section: Discussionmentioning
confidence: 93%